Pengunaan Level Tepung Tapioka dalam Pembuatan Wafer Amoniasi Kulit buah Kakao terhadap Kandungan Bahan Kering, Bahan Organik, Protein Kasar - fridarti fridarti; Nofriwan Nofriwan; Sri Mulyani (Fakultas Pertanian Universitas Tamansiswa Padang, 2021)
Ammonation Wafers of Cocoa pods on Dry Ingredients (BK), Organic Ingredients (BO), Crude Protein (PK). The feed ingredients used in making the Ammonation Wafer of Cocoa pods in this study consisted of: cocoa pods and Gamal Leaves. The feed ingredients are formulated according to the feed in the manufacture of Cocoa pods Ammonia Wafers (10%), (15%), (20%), (25%) and then discussed in the form of Cocoa pods Ammonia Wafers. (70% Cocoa Skin, 30% Gamal). The equipment used consists of equipment such as coals, pans, bowls, large spoons, small spoons and machetes for chopping and proximate testing. The experimental design used is a completely randomized design (CRD), consisting of 4 Wafers + 30% Gamal, P2 = Cacao Skin Ammonia Wafer 15% Tapioca + 30% Gamal P3 = Cacao pods Ammonia Wafer 20% Tapioca + 30% Gamal and P4 Wafer Cacao Ammonation Skin Wafer 25% Tapioca + 30% Gamal. The data obtained were analyzed by ANOVA. Ammonation Wafer of Cocoa pods, Data obtained were analyzed by variance analysis (ANOVA). The results showed that the Tapioca Flour Level Research in making the Amoniation Wafer Cocoa pods (P <0.05) was not real against Dry Ingredients (BK), (P <0.05) was completely unsuccessful against Organic Ingredients (BO), (P <0.05) assume no real Against Crude Protein (PK). Increase Tapioca Flour in the Making of Cocoa Skin Ammonia Wafers. Not significant effect on the value of Dry Ingredients, Organic Ingredients, and Crude Protein.